ASPEK KEJIWAAN TOKOH DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL THE CHRONICLE OF KARTINI KARYA WIWID PRASETYO SERTA RELEVANSINYA DENGAN BAHAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Purika, Dintya Ayu; Andayani, Andayani; Sumarlam, Sumarlam (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This research described the novel The Chronicle of Kartini work wiwid prasetyo in terms of (1) the structure novel includes: the theme, figures and penokohan and the message of in the novel the chronicle of kartini work Wiwid Prasetyo; (2) aspects psychiatric a figure in the novel The Chronicle of Kartini work Wiwid Prasetyo; (3) described and explains value character education in the novel The Chronicle of Kartini work Wiwid Prasetyo; (4) described and explains relevance study the novel The Chronicle of Kartini work Wiwid Prasetyo with learning the indonesian language in high school. The research is research descriptive qualitative with the methods content analysis (analysis the contents of/analysis a document). This research result indicates that the theme contained in a novel as a broad outline highlight education related to history education figures indonesian women, R.A. Kartini. Psychiatric aspects figures according to the theory needs abraham maslow includes: a physiological need, the safety, the mutual having and loved, the awards (esteem), and needs aktualisasi themselves. The character education that are more dominant in this novel, the hard work. A novel it has relevance to learning the indonesian language in high school.